ANTESEDEN EARNING PER SHARE PADA PERUSAHAAN PROPERTI DAN REAL ESTATE YANG TERDAFTAR DI BEI - Hendra Utama (Jurnal Abdi Ilmu, 2020)
This study aims to find out how the influence of firm size (X1) and debt to assets ratio (X2) on earnings per share in property and real estate companies listed on the Indonesia Stock Exchange, either partially or simultaneously. The research data used is data from property and real estate companies during 2014-2018. The population in this study amounted to 55 property and real estate companies with a sample of 41 companies. The results showed that firm size had no significant effect on earnings per share, while debt to assets ratio had a positive and significant effect on earnings per share. Simultaneously, firm size and debt to assets ratio have a positive and significant effect on earnings per share.